PWE-020 Catheter-associated complications including deep vein thrombosis in a HPN cohort: the leicester intestinal failure team. (June 2019) - Samani, Syazeddy; Kodali, Karuna; Baker, Melanie; Rogers, Dan; Stewart, James
Abstract : Introduction: Deep vein thrombosis (DVT) is a recognized complication associated with central catheters and it is thought that peripherally inserted central venous catheters (PICC) were associated with higher rates compared to centrally inserted catheters (CVC) but studies performed were not always in patients with home parenteral nutrition (HPN). 1, 2 The aim of our analysis is to assess the incidence of catheter-associated deep vein thrombosis (CA-DVT) and evaluate different rates of catheter-associated complication (CA-C) between the PICC and CVC group in a HPN cohort. Method: This is a retrospective, single centre cohort analysis of patients on HPN who had either PICC or CVC. The number of catheters removed due to CA-C from the 1st of January 2018 to 31st of December 2018 was reviewed and expressed in episodes. Data on CA-C which consisted of CA-DVT, confirmed and suspected catheter-associated infection (CA-I), catheter-associated device dysfunction (CA-DD) including line fracture and occlusion were analysed. Rates were calculated based upon the number of catheter and catheter re-inserted during this time period. Cumulative episodes and rates were compared between the two groups. Fisher's exact test was used for statistical analysis. Results: 64.3% (n=45) had CVC (Hickman lines) and 35.7% (n=25) had PICC with 25 episodes of catheter removal (n=19 and n=9 respectively, multiple episodes per patient allowed). The overall rate of CA-DVT was low at 1.4% (n=1) and this was associated with a PICC. There was no reported deep vein thrombosis within the CVC group. The cumulative episodes of CA-C appeared higher in the CVC group compared to the PICC group although the difference in rates was not statistically significant (42.2% n=19 vs 36%n=9, p = 0.7994). There were 9 episodes of CA-I and 10 episodes of CA-DD in the CVC group compared to 3 episodes of CA-I and 5 episodes of CA-DD in the PICC group. Statistical analysis showed no difference in rates of CA-I (p=0.5029) or CA-DD (p=1) between the two groups. Conclusions: This analysis showed an overall low rate of catheter-associated deep vein thrombosis within a HPN cohort in a 12 month period. There was no significant difference in rates of catheter-associated complication between PICC and CVC. References: Bonizzoli M, Batacchi S, et al. Peripherally inserted central venous catheters and central venous catheters related thrombosis in post-critical patients. Intensive Care Med . 2011;37(2.:284. Vineet Chopra et al. Risk of venous thromboembolism associated with peripherally inserted central catheters: A systematic review and meta-analysis. The Lancet. 2013;vol 382 issue 9889; 31–25.